Nivolumab-induced oral and cutaneous bullous pemphigoid: A case report - Sturque Julie; Boralevi Franck; Fricain Jean-Christophe (EDP Sciences, 2019)
Introduction: Nivolumab-induced oral and cutaneous bullous pemphigoid have been rarely reported in the literature. Observations: A 64-year-old male patient was treated with nivolumab for melanoma. He presented with oral lesions in the palatal and gingival mucosal lesions. Nine months after the initiation of nivolumab therapy, a cutaneous bullous pemphigoid was found on his right forearm. The level of anti-BPAG2 (or anti-BP 180) was positive with a rate of 83 AU/mL, thereby confirming the diagnosis of bullous pemphigoid. His oral mucosa, first in the posterolateral area of the palate and then in the gingiva, was affected 3 months later. Histological examination revealed a subepidermal bulla with few eosinophils. Comments: Nivolumab is a novel monoclonal human antibody used to potentiate T cell responses, particularly anti-tumor responses. The first diagnosis considered was lichen planus, and it has been excluded from this study based on histological results. Right from lesion onset after treatment initiation, nivolumab was strongly suspected to cause these mucocutaneous lesions. To investigate the causes and effects of nivolumab-induced oral and cutaneous bullous pemphigoid, it would be necessary to record the regression of these lesions at the end of treatment; however, this is not possible due to ethical reasons. The treatment of lesions primarily involves corticosteroid usage; however, rituximab is also used. Conclusion: Oral surgeons must consider the oral side effects of novel targeted therapies, including those of immunological checkpoint inhibitors.